EXPLORING THE BIOLOGICAL PROTECTIVE ROLE OF CAROTENOIDS BY RAMAN SPECTROSCOPY: MECHANICAL STRESS OF CELLS - NEKVAPIL, F.; MÜLLER MOLNÁR, CS.; TOMŠIĆ, S.; CINTĂ PINZARU, S. (Studia Universitatis Babeș-Bolyai Physica, 2019)
Carotenoids present a group of tetraterpenoid biomolecules which are well known for their physiological benefits through their remarkable radical scavenging activity and reactive oxygen species quenching. However, little is known about role of carotenoids in relieving mechanical stress. Hence, in this study, we exposed sea urchin fertilized eggs to mechanical stress in form of centrifugation and exploited the advantage of Resonance Raman scattering to probe if the carotenoid profile or their distribution would change after application of the stress. Silver nanoparticles were used ro probe the Raman signal of carotenoids near the cell surface and attempt to achieve SERRS conditions (Surface-enhanced Resonance Raman scattering). We have found that carotenoid concentration notably increased on the cell surface after centrifugation, indicating that carotenoids were mobilized in response to mechanical stress.